Weight loss before conception: effects on atherogenic apolipoprotein lipid particles and endothelial function during pregnancy - Robert A. Wild, M.D., Ph.D.; Daniel Zhao, Ph.D.; Michael J. McPhaul, M.D.; Rodney K. Edwards, M.D.; Karl R. Hansen, M.D., Ph.D.; Elizabeth L. Wolfe, M.D.; David S. Wrenn, Ph.D. (F&S Reports)
Objective: To assess atherogenic apolipoprotein lipids and markers of vascular function in pregnancy after prepregnancy weight loss. Design: Retrospective cohort study. Subjects: The weight loss cohort included pregnant women who achieved prepregnancy weight loss, and the weight gain cohort consisted of those who gained weight before pregnancy. All patients became pregnant after enrolling in the randomized clinical trial “Improving Reproductive Fitness Through Pretreatment with Lifestyle Modification in Obese Women with Unexplained Infertility” and delivered a single live birth at ≥36 weeks of gestation. Exposure: Prepregnancy weight loss. Main Outcome Measures: Apolipoprotein lipid levels. Results: Prepregnancy weight loss was associated with lower atherogenic apolipoprotein lipid levels during pregnancy and better indicators of vascular function. Conclusion: Our findings suggest that encouraging prepregnancy weight loss in obese women leads to improved vascular function during pregnancy. Prepregnancy weight loss has significant implications for healthcare professionals because it underscores the potential benefits of weight loss interventions in reducing the risk of cardiovascular disease for women who become pregnant.